Pengaruh Terapi Pijat Kaki Pada Pasien Coronary Artery Disease (CAD) Non Stemi Terhadap Kualitas Tidur Di Ruangan CVCU RSUD Prof. Dr. H. Aloei Saboe Kota Gorontalo - Monoarfa, Susanty; Damansyah, Haslinda; Oktaviani, Fitriyanty (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Foot massage is a technique that can teach blood circulation, give a sense of relaxation to the body, relieve stress, relieve fatigue and practice by applying pressure at certain points, massage makes the blood circulation smooth so that it will improve the function of the problematic organs. Methods: This article is pre-experimental research with one group pre-test and post-test design, Theobject of the study was a patient in the CVCU room of RSUD Prof. Dr.H. Aloei Saboe. The subject of study is the subject intended to be researched by the author or the subject that is the center of attention or target of the researcher. The subjects in this case study were patients in the CVCU room of RSUD Prof. Dr. H. Aloei Saboe as many as 12 respondents with the criteria of patients who experience Coronary Artery Disease (CAD), and patietn experience poor sleep quality. The research instrument uses kuisoner PSQI (Pittsburgh Sleep Quality Index). Results: Based on the results obtained, it was found that in assesssin sleep quality pre and post intervention, the statistical result was p-value = 0.000. For th assessment of the pre and post-intervention sleep latency, the statistical reslut was p-value = 0.002. In assessing sleep duration pre and post intervention, the statistical result was p-value = 0,000. In assessing daily sleep efficiency pre and post intervention, the statistical result was p-value = 0,000. Meanwhile, for the assessment of pre- and post-intervention sleep disorders, the statistical result was p-value = 0.017, which means there was a significant chage after foo massage therapy on sleep quality in Coronary Artery Desease (CAD) patients. Conclusion: It is hoped that foot massage therapy can be appliend to sleep quality to improve the quality of sleep that patients have the ICU Room of RSUD Prof. Dr. H. Aloei Saboe Gorontalo City.